Technical report: modelling of chlorine decay rates based on initial chlorine and reactant concentrations in the water distribution system / Nur Syahira Ahmad, Nurul Ezawana Mohamad Tosrin and Farah Amanina Normahadi - Ahmad, Nur Syahira; Mohamad Tosrin, Nurul Ezawana; Normahadi, Farah Amanina (2018)
Chlorination is one of the method that can be used to disinfect water. Chlorination is important to maintain the water quality in distribution system through a chlorine residual. Chlorine decay in bulk water need to be described clearly to understand the decay characteristics. Second order model for modelling reaction rate variation with respect to initial chlorine concentration was found to be one of the most suitable model for this purpose. This model is developed following a first order reaction. The model is used to determine the rate of variation bulk decay rates of chlorine residuals. In this project, an analytical solution for this model was developed by assuming that the initial phase using the second order decay equation to find decay constant C₀ and the rate of reaction for the bulk decay of chlorine, kd. From the data obtained we use Microsoft Excel to build the graph.